503 Separating the Associations of Programming and Tracking during Infancy with Childhood Blood Pressure, the Abcd Study. (October 2012) - Beer, M de; Eijsden, M van; Vrijkotte, T; Fall, C; Osmond, C; Gemke, R
Abstract : Background and Aims: In a prospective pregnancy cohort study, we investigated the association of early growth with blood pressure at 5–6 years of age. Methods: Our study was based on 2, 338 children who were born healthy at ≥ 37 completed weeks gestation with on average 7 measures of growth (weight and length) from birth to age 12 months. We used conditional weight, a residual of current weight regressed on prior weights, to represent deviations from expected weight gain from 0 to 1, 1 to 3, 3 to 6, and 6 to 12 months. The same method was applied for conditional length and body mass index. Associations of these measures with systolic and diastolic blood pressure at the age of 5–6 years were modeled before and after adjustment for current body mass index and height. Results: Higher weight-, length-, and bmi conditionals (expressing faster growth) were associated with higher blood pressure, with the exception of conditional growth between birth and 1 month. Adjusted for current height and body mass index, almost none of the conditionals were associated with blood pressure. However, lower birth weight and lower weight and height conditionals 0 to 1 month were associated with higher systolic blood pressure at age 5–6 years. Conclusions: We infer that the inverse association between prenatal and first month growth with childhood blood pressure may reflect a programming effect, while the positive association between infant growth after 1 month with childhood blood pressure probably reflects an effect of the tracking of body size.